A study of morphology and Human epidermal growth factor receptor (HER2) expression in gastroesophageal junction and gastric adenocarcinoma (Journal of Pathology of Nepal, 2025)
Background: HER2 overexpression in gastric cancer varies depending on tumor histology and anatomical location. This study aimed to score and evaluate the immunohistochemical marker HER2 in gastric adenocarcinoma and also to compare the expression of HER2 between gastro-oesophageal and gastric adenocarcinoma.Materials and Methods: A cross-sectional, retrospective study was conducted on 44 cases of histopathologically proven gastro-oesophageal and gastric adenocarcinoma by endoscopic Biopsy (41 cases) and gastrectomy (7 cases) specimens.  Out of the 48 participants enrolled, we received both endoscopy and gastrectomy specimens from 4 cases. Hence, the analysis was based on the findings of 44 cases. HER2 immunohistochemistry was done on formalin-fixed paraffin-embedded tissues. Variables like age, gender, anatomical distribution of tumor, type of cancer, tumor grade and HER2 grade were studied.Results: Out of the 44 cases, the majority of the adenocarcinoma were gastric in origin [29/44 cases (65%)], with antral adenocarcinoma accounting for the largest proportion of gastric adenocarcinoma [12/29 cases (42%)]. HER2 overexpression was seen in 6/44 cases (14%) of the total cases. Well-differentiated adenocarcinoma showed maximum HER2 expression [4/8 cases (50%)] compared to moderately differentiated and poorly differentiated adenocarcinomas.Conclusions: HER2 overexpression is more frequent in well-differentiated gastric and gastro-esophageal adenocarcinomas, and in gastro-esophageal junction adenocarcinomas than in gastric adenocarcinomas.